Ahmet Rıfat Efendi's Mirâtü’l-Mekâsid : the possibility of a Sunni Bektaşiyye in the nineteenth century - Kiper, Metin. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
This thesis focuses on the work Mir’âtü'l-Mekâsid fî Def'i'l Mefâsid, which was written by a Bektaşi intellectual, Ahmet Rıfat Efendi in 1875. Although the Bektaşi order left its mark on the Ottoman Empire and had a long-standing association with the Janissary corps, it was also known for its heterodox and non-Sunni orientation. Yet, in Mir’âtü'l-Mekâsid, the author describes a Sunni Bektaşiyye. In this work, the Bektaşi order is represented as a Sufi order that was no different from the other Sunni Sufi orders. In particular, the author's efforts to bring together the Halidi branch of the Nakşibendi order and the Bektaşi order stand out. Why did Ahmet Rıfat Efendi represent Bektaşis in this way? This thesis argues that the answer to this question lies in the new challenges faced by Bektaşis in the nineteenth century. In 1826, the Bektaşi order was abolished along with the Janissary corps and many Bektaşi lodges were destroyed or given over to Nakşibendi sheikhs. Despite these setbacks, however, the Bektaşi order could survive and gradually recuperated. Yet, the attacks on the Bektaşis did not cease. In 1875, Harputlu Ishak Hoca penned a polemical work against the order. This thesis argues that Ahmet Rıfat Efendi penned his work in response to this and similar attacks and aimed to create. The necessary conditions and concessions for the Bektaşi order continue to exist in the late 19th -century Ottoman world.
Keywords: Ahmet Rifat, d. 1876.; Bektashi.